Motivation and academic desertion in Peruvian medical students - Bermúdez García, Alejandro (2016)
In the special issue 2015, volume 76 of its prestigious journal, the short communication was published: "Student desertion in science careers health in Peru," Heredia et al (1). In this communication, it shows a real problem that occurs not only in our country, in relation to the training of human resources in health: desertion. We agree that the problem is multifactorial and often the impact of this decision is final, not only for students but for the family environment that had certain expectations and see how you lose your investment in time and resources; just as society does, by providing the opportunity for training, leaving aside other person who applied and did not get that vacancy wasted.